High Temperatures and Their Relationship With Numerical Achievement for 10000m Advance Runners - Naser, Sadoun (Journal of Physical Education, 2016)
The problem of the research lies in the decline in numerical achievement of Iraqi runners especially 10000m runners during summer time (hot days) compared to their own achievements in other seasons during moderate temperature. The researcher conducted two tests each in a different temperature to find the effect of temperature on 10000m advance runners' achievement. The subjects were Iraqi champion 10000m runners. The data was collected and treated using proper statistical methods. The results showed the negative effect of high temperature during competitions on the 10000m runner's achievement. The researcher recommended conducting long distance running in Iraq during moderate temperature.